MOLECULAR DIAGNOSIS OF TRYPANOSOMA EVANSI INFECTION INCAMELUS DROMEDARIUS FROM EASTERN ANDWESTERN REGIONS OF THE SUDAN - Ali, Nahla O. M.; Croof, Hamid I. M. N.; Abdalla, Hamid S. (Emirates Journal of Food and Agriculture, 2011)
Trypanosoma evansi infection is the most important disease of Camel in the Sudan. The present work was carried out to evaluate a simple PCR-based technique for field diagnosis of T. evansi infection in camels from Eastern and Western regions of the Sudan. A representative number of 600 camels (Camelus dromedarius) from different areas of Gedarrif State (Eastern) and North Kordofan State (Western) were examined from May 2005 to July 2007 for Trypanosoma evansi infection. The tests used were parasitological (Wet Smear Film, WSF; Thin Smear Film, TSF; Buffy Coat, BC), serological (Card Agglutination Test/T. evansi, CATT), and DNA amplification by polymerase chain reaction (PCR). The prevalence of T. evansi infection in camels was detected in 36 (out of 40), 100 (out of 210), 36, 22, 10 (Out of 600); by PCR, CATT, TSF, BC and WSF with sensitivity of 90%, 47.6%, 6%, 3.7% and 1.7%, respectively. PCR revealed a specific 200 bp band in positive samples. The intensity of PCR bands was variable in different test samples depending upon the level of infection in the test samples. The history of intermittent fever, emaciation, oedema, poor body condition significantly correlated with positive serological status in CATT as well as trypanosome DNA detection by PCR. As there are no previous studies in the Sudan on the molecular characterization of the parasite, this research is useful in formulating strategic control programmes.